Histórias em quadrinhos: uma alternativa pedagógica para o ensino de química - Klein, Vanessa (2018)
Due to the complexity of Chemistry teaching, one of teachers‟ challenges relies on the constant search for alternatives to innovate the educational context, in order to arouse students‟ interest and flexibilize the teaching learning process. From this perspective, the present paper, developed within the conceptions of the research Development of Educational Technologies in Network, of the Post-Graduate Program in Educational Technologies in Network of the Federal University of Santa Maria (UFSM), aims to potentialize and innovate the teaching and learning of chemistry concepts through the production of comic books related to content addressed to in the discipline of Agronomy Chemistry – QMC 1032, of UFSM‟s Agronomy graduation course. The method used in this research was the Design Based Research, in which the research subjects were 65 students of the first semester of UFSM‟s Agronomy graduation course, being 39 male and 19 female subjects, with ages between 17 and 23 years old, enrolled in the discipline QMC 1032 – Agronomy Chemistry. The research was developed in six stages: (1) analysis of the contents in which students presented greater difficulties in learning; (2) comprehension of the problem to be solved; (3) strategy definition to be implemented; (4) comic book planning; (5) comic books implementation through Facebook social media and the virtual teaching and learning environment Moodle, aiming to flexibilize and potentialize the learning of chemistry concepts; (6) application, replanning and availability of the source material in Ebook format. Toondoo ©, a tool where one can create and edit comic books, was used to elaborate the comic books, as well as wikis, online forums and e-books. The data was collected through written and digital registers, the latter by Moodle and Facebook. The results shows that comic book language is well accepted by students and it motivates them to read, once its illustrations provides more interest than conventional texts.